Syntheses and catalytic oxotransfer activities of oxo molybdenum(vi) complexes of a new aminoalcohol phenolate ligand. Issue 21 (18th May 2017) - Hossain, M. K.; Haukka, M.; Sillanpää, R.; Hrovat, D. A.; Richmond, M. G.; Nordlander, E.; Lehtonen, A.
Abstract : A novel trimeric complex [MoO2 (L)3 ] (L = tridentate aminoalcohol phenolate ligand) produces monomeric solvent adducts [MoO2 (L)(solv)] in coordinating solvents. All complexes have been investigated as catalysts in oxotransfer reactions. Abstract : The new aminoalcohol phenol 2, 4-di- tert -butyl-6-(((2-hydroxy-2-phenylethyl)amino)methyl)phenol (H2 L ) was prepared by a facile solvent-free synthesis and used as a tridentate ligand for new cis -dioxomolybdenum(vi )(L) complexes. In the presence of a coordinating solvent (DMSO, MeOH, pyridine), the complexes crystallise as monomeric solvent adducts while in the absence of such molecules, a trimer with asymmetric Mo{O→Mo bridges crystallises. The complexes can catalyse epoxidation of cis -cyclooctene and sulfoxidation of methyl- p -tolylsulfide, using tert -butyl hydroperoxide as oxidant.